Augmenting the ModelicaTM Ocean Engineering Toolbox to Support Multibody Dynamic Simulations (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Ocean wave energy shows enormous promise as a renewable energy source, offering an extensive and energy-dense resource. Despite this potential, WECs have not yet seen the same widespread commercial adoption as other renewable sources such as wind and solar. This is largely due to their technological immaturity, with most WEC devices residing at technology readiness levels (TRL) 3 through 5. At these medium TRLs, developers rely on mid-fidelity time-domain numerical modelling simulation tools, as they offer an accurate low-cost alternative to experimental testing.There are only a handful of publicly available dedicated WEC simulation tools, especially ones capable of representing wave-to-wire (W2W) models. Furthermore, many of these tools are only available through commercial licences, WEC-Sim™ being the only widely adopted open-source alternative which even requires a commercial MATLAB™/SIMULINK™ licence. There is a lack of accurate and computationally efficient W2W WEC numerical simulation tools, particularly one that is open-source and does not require additional commercial software.  In this work, we present the Ocean Engineering Toolbox (OET) – an open-source toolbox developed specifically to address this need.The OET is an open-source modelling and simulation toolbox developed by Sys-MoDEL™ and written in Modelica™ that is designed to simulate offshore structures including marine renewable energy (MRE) technologies. However, at present, only WEC technologies can be modelled, with a road map to incorporate tidal and offshore wind in future iterations. Previous works have established capabilities to represent the radiation state-space and excitation force spectral decomposition in regular and irregular wave conditions but were limited to a single body acting in one degree of freedom (DoF).This work addresses these limitations with an extensive overhaul of the existing codebase and integrating several key new features. Namely, the latest release introduces a comprehensive multibody dynamic architecture as well as additional components such as a: a) linear mooring, b) linear power take-off (PTO) and controller, c) viscous damping and drag, and d) equal energy method for frequency selection. Following the ethos of Modelica, this work integrates the principles of Object-Oriented Programming (OOP) to enhance code readability and reusability.Validation is performed by modelling the US Department of Energy’s (US DoE) Reference Model 3 (RM3) and using WEC-Sim as the benchmark. The requisite hydrodynamic coefficients are obtained from the WEC-Sim source code using the Boundary Element Method (BEM) solver WAMIT™. Preliminary simulations demonstrate good data coherence between the two tools.Although still early in development, the OET shows enormous potential to meet the demand for a fully open-source tool capable of efficiently conducting W2W simulations of various WEC archetypes.